The platelet Fc receptor, FcγRIIa. Issue 1 (November 2015) - Qiao, Jianlin; Al‐Tamimi, Mohammad; Baker, Ross I.; Andrews, Robert K.; Gardiner, Elizabeth E.
Summary: Human platelets express FcγRIIa, the low‐affinity receptor for the constant fragment (Fc) of immunoglobulin (Ig) G that is also found on neutrophils, monocytes, and macrophages. Engagement of this receptor on platelets by immune complexes triggers intracellular signaling events that lead to platelet activation and aggregation. Importantly these events occur in vivo, particularly in response to pathological immune complexes, and engagement of this receptor on platelets has been causally linked to disease pathology. In this review, we will highlight some of the key features of this receptor in the context of the platelet surface, and examine the functions of platelet FcγRIIa in normal hemostasis and in response to injury and infection. This review will also highlight pathological consequences of engagement of this receptor in platelet‐based autoimmune disorders. Finally, we present some new data investigating whether levels of the extracellular ligand‐binding region of platelet glycoprotein VI which is rapidly shed upon engagement of platelet FcγRIIa by autoantibodies, can report on the presence of pathological anti‐heparin/platelet factor 4 immune complexes and thus identify patients with pathological autoantibodies who are at the greatest risk of developing life‐threatening thrombosis in the setting of heparin‐induced thrombocytopenia.